2016
DOI: 10.1155/2016/2096797
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Thai Herbal Prasaplai Formula for Treatment of Primary Dysmenorrhea: A Short‐Term Randomized Controlled Trial

Abstract: This study aims to compare the efficacy of pain relief between a specific Thai herbal Prasaplai formula (PPF) and placebo in patients with primary dysmenorrhea. Forty women with primary dysmenorrhea symptoms were randomized into two groups. The experimental group received PPF capsules 1000 mg orally three times per day before meals for three days starting from the first day of menstruation. The placebo group received placebo as the same dose and time. Average pain intensity from the first day to the third day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It was found that most herbs in Prasaplai exhibit anti-inflammatory effects, especially Plai ( Zingiber cassumunar ), and Prasaplai extracts possess COX inhibitory activity [ 32 ]. These have led to clinical studies proving a new indication of anti-dysmenorrhea [ 33 ], which has been successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that most herbs in Prasaplai exhibit anti-inflammatory effects, especially Plai ( Zingiber cassumunar ), and Prasaplai extracts possess COX inhibitory activity [ 32 ]. These have led to clinical studies proving a new indication of anti-dysmenorrhea [ 33 ], which has been successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…Zingiber cassumunar (ZC) Roxb. known as Plai, is one of the Thai herbal formulas which is used for restoring body elemental balance [2]. It is used for the treatment of menstrual disorders, flow enhancement of the discarded uterine blood after birth, wound healing, muscle and joint pain, skin diseases, inflammation, and abscesses [3].…”
Section: Introductionmentioning
confidence: 99%
“…ZC Roxb. is a major component of the Prasaplai recipe, a Thai traditional medicine formula, which has been used to relieve pain from the primary dysmenorrhea, regulates irregular menstrual flow, and driving out the discarded uterine blood after birth [2,4]. Prasaplai recipe has been listed in the Thai traditional common household drug list since 2006 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Primary dysmenorrhea (PD) is a common gynecological disorder. Menstrual pain typically begins during or just prior to menses [ 1 , 2 ]. The prevalence of PD is highest in adolescent girls and women of reproductive age, with estimates ranging from 20 to 90% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%